2021
DOI: 10.1097/md.0000000000024617
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian diet in dialysis patients

Abstract: Nutritional status is a predictor of mortality and morbidity in dialysis patients. This study aimed to assess dietary behaviors in dialysis patients compared to the recommendations of the Kidney Disease Outcomes Quality Initiative. Ninety five dialysis patients recruited from a hospital completed a 24-hour dietary recall questionnaire. Body weight, energy requirements, protein requirements, albumin, normalized protein catabolic rate, and 25(OH) vitamin D levels were measured. Of the 95 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The results indicated that over half of the patients had insufficient protein and energy intake, consistent with previous studies [ 29 , 30 ]. Compared to Cupisti et al.’s study [ 31 ], the dietary potassium intake of MHD patients in this study was significantly lower, possibly due to different dietary habits regarding potassium-rich foods in China.…”
Section: Discussionsupporting
confidence: 91%
“…The results indicated that over half of the patients had insufficient protein and energy intake, consistent with previous studies [ 29 , 30 ]. Compared to Cupisti et al.’s study [ 31 ], the dietary potassium intake of MHD patients in this study was significantly lower, possibly due to different dietary habits regarding potassium-rich foods in China.…”
Section: Discussionsupporting
confidence: 91%
“…Subih et al [25] confirmed the prevalence of inadequate 25(OH)D3 levels in HD patients, with concentrations <30 ng/mL before the study began. Chen et al [26] found that 80% of patients had insufficient vitamin D levels (25(OH)D3 < 30 ng/mL) and 11.6% had severe deficiency (25(OH)D3 <10 ng/mL).…”
Section: Discussionmentioning
confidence: 99%